2013
DOI: 10.1002/suco.201200021
|View full text |Cite
|
Sign up to set email alerts
|

Design for service life: implementation of fib Model Code 2010 rules in the operational code ISO 16204

Abstract: CEB/FIP Model Code 1990 (MC-1990 [1] Structures 2010 (MC-2010 [5,6,7] BackgroundDurability of concrete structures, and in particular the lack of such, has been in the focus of society in general over the last few decades. Excessive repair needs have challenged our industry. The traditional approach in most national and regional concrete standards is to specify the provisions to ensure a certain design service life by limiting values for material composition and geometry based on the expert opinion of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 3 publications
2
12
0
1
Order By: Relevance
“…Both the origin and the values of this crack width limit are questionable, as was so well stated by Helland [56]: "Intuitively we assume that cracked structures will deteriorate faster than uncracked structures. However, neither the fib nor the ISO committee was able to come up with any general model to take this effect into account."…”
Section: Effect Of Crack Width On the Corrosion Processmentioning
confidence: 96%
“…Both the origin and the values of this crack width limit are questionable, as was so well stated by Helland [56]: "Intuitively we assume that cracked structures will deteriorate faster than uncracked structures. However, neither the fib nor the ISO committee was able to come up with any general model to take this effect into account."…”
Section: Effect Of Crack Width On the Corrosion Processmentioning
confidence: 96%
“…In order to be able to apply the probabilistic approaches to the service life of a tunnel, we need models describing these deterioration processes over time. But at present, no time‐dependent models for these cases with general international consensus are available, as is concluded by the fib Model Code for Concrete Structures 2010 and ISO 16204 . Consequently, these deterioration processes are not taken into account in this research.…”
Section: Probabilistic Degradation Modellingmentioning
confidence: 99%
“…Experiments conducted by Cabrera [15] and Ballim/Reid [16] concluded that the corrosion percentage C perc and the deflection ratio D r are linearly related. The linear regression function for a Portland cement concrete beam given by Cabrera is adopted in this study: [29]. Consequently, these deterioration processes are not taken into account in this research.…”
Section: B) Relationship Between Deflection Ratio and Corrosion Severitymentioning
confidence: 99%
“…Since steel corrosion is an expansive reaction, it will then lead to cracking and spalling of the concrete cover [ 4 , 5 ]. As a consequence, service life design guidelines require that the concrete cover to the reinforcement is of a certain dimension and quality [ 6 , 7 ]. These guidelines are, however, derived assuming that the concrete cover is uncracked.…”
Section: Introductionmentioning
confidence: 99%